POLA DAKWAH MUHAMMADIYAH DI KOTA BANJARMASIN - Riady, Fahmi (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 10 No 1 (2014), 2014)
This paper examines the pattern of Muhammadiyah’s preaching in Banjarmasin. Of Islamic organizations in this city, Muhammadiyah has a large base of masses since dakwah has been carried out consistently and continuously.  Muhammadiyah of  Banjarmasin has two models in doing da’wah activities. First, internal da’wah model, which is done in a various ways such as verbal (bil lisan), writing (bil kitabah) or behaviour (bil hal), directed to a group of people belong to Muhammadiyah. This also includes consolidation of the members of Muhammadiyah. Second, external da’wah model, which is directed to non-Muhammadiyah’s members.